Halliday’s Discourse Analysis of the "Tatap" Exhibition - Haryono Haryono; Christofer Satria; Taufik Mawardi (Gorga : Jurnal Seni Rupa, 2024)
Painting exhibitions are part of a discourse strategy published by artists through public spaces. Where art exhibitions generally try to represent multi-dimensional values in the form of artwork from various types of spaces. Exhibitions are seen as art events that are discoursed in the form of exhibition packages with the theme "Tatap". Tatap is the concept of Ahmad Junaidin's solo exhibition which consists of three categories of small sub-themes, namely the theme of nature, the theme of Sasak mythology, and the theme of tradition. Behind the exhibition with the theme "Tatap" of course, there is another purpose that must be conveyed by the discourse to the audience. The purpose of this study is to try to describe the existence of the dimensions of the artist's paintings that are exhibited and the curatorial dimensions presented in the form of a narrative of the relationship between works and paintings are dimensions that are related to one another. Because behind the text, both visual and verbal, there are certain intentions and purposes. This study uses a qualitative research type with the Halliday discourse analysis research method consisting of the field of discourse (field of discourse) what is being discussed, the discourse participants (tenor of discourse) who are involved in the conversation, and the mode of discourse (mode of discourse) the choice of language used by the media. The results of the study show that what is exhibited and what is opined experience distortion between the work and its curatorial.